Catalytic deAMPylation in AMPylation-inhibitory/assistant forms of FICD protein - Liu, Meili; Li, Li; Wang, Zhiqin; Wang, Shuang; Tang, Xiaowen (Frontiers in Chemistry, 2023)
DeAMPylation, as a reversible reaction of AMPylation and mediated by the endoplasmic reticulum-localized enzyme FICD (filamentation induced by cAMP domain protein, also known as HYPE), is an important process in protein posttranslational modifications (PTMs). Elucidating the function and catalytic details of FICD is of vital importance to give a comprehensive understanding of protein folding homeostasis. However, the detailed deAMPylation mechanism is still unclear. Furthermore, the role of a conserved glutamine (Glu234), that plays an inhibitory role in the AMPylation response, is still an open question in the deAMPylation process. In the present work, the elaborated deAMPylation mechanisms with AMPylation-inhibitory/assistant forms of FICD (wild type and Glu234Ala mutant) were investigated based on the QM(DFT)/MM MD approach. The results revealed that deAMPylation was triggered by proton transfer from protonated histidine (His363) to AMPylated threonine, instead of a nucleophilic attack of water molecule adding to the phosphorus of AMP. The free energy barrier of deAMPylation in wild type ( 17.3 kcal/mol) is consistent with that in Glu234Ala mutant of FICD ( 17.1 kcal/mol), suggesting that the alteration of Glu234 residue does not affect the deAMPylation reaction and indirectly verifying the inducement of deAMPylation in FICD. In wild type, the proton in nucleophilic water molecule is transferred to Glu234, whereas it is delivered to Asp367 through the hydrogen-bond network of coordinated water molecules in Glu234Ala mutant. The present findings were inspirational for understanding the catalytic and inhibitory mechanisms of FICD-mediated AMP transfer, paving the way for further studies on the physiological role of FICD protein.